Casa São Félix - textos e projecto para duas casas em construção - Inês Sofia Beleza de Azevedo (2017)
This dissertation celebrates the beginning of a cycle of learning that follows the academic course and that inserts us in the scope of the practice of project in real context.The first approach to this new reality - a project for a house that carries restlessness, doubts and reflections with it - is revisited in order to think about the conflict that has been established between us, architects, and the unfolding of the creative process, when external factors such as the client or municipality instructions, are included in the problematic of the project and threat a stability that until then had been seen as undisturbable.A narrative of texts, images and drawings is assembled that, taking this particular house as its case study, intuit about phenomena that is transversal to any type of construction.To give meaning to what has been done, so that one can come to do better. To look at the work done and create distance from it.The method is that of deviation: we move away from the project and then return to it. Along the way, we look at images (which can be figurative, literary...) that are used as metaphors.The problem is transferred from one field to another, connections are drawn between various disciplines, we are led by the enchantment of bringing together things that were not previously linked. Then, once all the experiences of the path traveled are united, one arrives home.The result is a clearer understanding of the meaning, realities, problems, and possibilities of architectural design. And, because folded upon itself, this study could not fail to be, also, a construction of me, as an architect citizen.